The Effect OK5R Strategy On Students' Achievement In Reading Comprehension - Simbolon, Ferry Irawan (The Explora, 2020)
Reading comprehension is a skill and knowledge that the students must understand and can use to find the text's central idea. Based on the researcher observation, almost all of the students at SMKN 2 Panyabungan faced reading comprehension difficulties. The researcher applied (OK5R Strategy) to know the effect on students' reading comprehension of descriptive text at the SMKN 2 Panyabungan. This research uses a quantitative method with experimental research and for collecting data using observation and tests. The sample used in this research is XI TB1, as the experimental class consists of 20 students, and XI TM1 as the control class consists of 20 students. The technique of sampling in this research is a saturated sampling. This research OK5R Strategy positively affects students' achievement in reading comprehension at eleventh-grade students SMKN 2 Panyabungan. Based on the result, the teacher can practice this strategy in the learning and teaching process.